Economic Pragmatism of Yogyakarta Muslim Community in Selecting Banking Institutions - Itsla Yunisva Aviva; Misnen Ardiansyah; Syafiq Mahmadah Hanafi (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
This research discusses the motives of the Muslim community in choosing banking institutions by using the analysis of pragmatism theory. This research is qualitative research using a phenomenology approach. Data collection that is used in this research is the interview, observation, and documentation. The result of the study indicated that the Muslim’s customer of Yogyakarta tend to be pragmatic due to the character of society which has more accommodating and flexible philosophy of life (tolerance). This pragmatic attitude was influenced by the internal factors (cognitive limitations) and external factors (reputation and service of Conventional Banks). Furthermore, adopting from the theory of Schutz’s motives that the motives reason (because of motive) of Yogyakarta's Moslem customers in choosing to the bank are their inconsistency in choosing is influenced by economic and service motives that are stronger than religious motives. As for their destination motive (in order to motive) namely fulfilling their needs.